THE EXTENT OF MARITIME TERRORISM AND PIRACY: A COMPARATIVE ANALYSIS - Joubert, Lydelle (Scientia Militaria - South African Journal of Military Studies, 2013)
Political and socio-economic factors led to the resurrection of piracy during the 1970s. By 1983, the problem became alarming, leading to the adoption of anti-piracy measures by the international community. During the same period, maritime terrorist attacks increased, although incidents remained localised. As insurgent movements fought on land to gain independence from former colonial governments, terrorist actions spilled into the maritime domain. The attacks on the USS Cole in 2000 and on the French-registered oil tanker, Limburg, in 2002 coupled with the terrorist attacks on the United States of America (US) on 11 September 2001 (9/11), created fear that a captured ship could be used as a delivery platform for weapons of mass destruction (WMD) or that a ship with dangerous cargo could be used as a weapon. No exclusively maritime terrorist organisations exist today. Maritime terrorism is only one of the areas of operation for terrorist organisations. Links between maritime pirates and terrorists are also limited, as the objectives of these organisations differ. Pirates have financial motives, while terrorists have political motives. Although cooperation between these groups is unlikely, it is not impossible and could be dangerous especially in vulnerable areas such as the coast of Somalia, the Red Sea and the Gulf of Aden.